Pengaruh Pemberian Sludge terhadap Pertumbuhan dan Hasil Tanaman Bayam Cabut (Amaranthus tricolor L.) dengan Tiga Kali Penanaman - Pardosi1, Roy Gom-Goman; Murniati, Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
plants with three planting times and determine the best dose of sludge. This research was conducted at the Faculty of Agriculture Experimental Garden, University of Riau. This study was carried out for three months starting from March 2018 to May 2018. This research was conducted experimentally and was prepared using a Completely Randomized Design (CRD) with sludge dose treatment consisting of 4 levels S1 = 5 tons / ha, S2 = 10 tons / ha, S3 = 15 tons / ha, S4 = 20 tons / ha. Each treatment was repeated 5 times. Data obtained from observations were analyzed statistically using variance and then tested further by Duncan's test for the New Multiple Range Test (DNMRT) at the level of 5%. From the results of the study it can be concluded that the provision of sludge at a dose of 6 kg / 3 m2 resulted in the best growth and yield of spinach plants, both first, second and third planting and increased sludge dose significantly increased plant height, number of leaves and fresh weight of plants.Â Keyword: Spinach, sludge